ANALISIS HARMONISA ARUS DAN TEGANGAN DARI VARIABEL SPEED DRIVE (VSD) TERHADAP PROFIL TEGANGAN DI JARINGAN DISTRIBUSI PT. PLN ULP TOMOHON MELALUI STUDI SIMULASI SOFTWARE ETAP - Novitri Taroreh; Janne Deivy Ticoh; Viverdy Memah; Fransiskus Seke; Ridwan Ridwan; Jocke Rapar (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2026)
Power quality is a critical factor in maintaining the reliability and efficiency of modern power systems, particularly in distribution networks that extensively utilize power electronic equipment. One of the primary sources of harmonic distortion is the use of Variable Speed Drives (VSDs), which operate as non-linear loads and cause current and voltage waveforms to deviate from their ideal sinusoidal shape. This study aims to analyze the harmonic characteristics generated by VSDs in the distribution system of PT. PLN ULP Tomohon, determine the levels of Total Harmonic Distortion of current (THD-I) and voltage (THD-V), and evaluate the effectiveness of harmonic mitigation using a passive single-tuned harmonic filter. The research employs a descriptive quantitative approach through modeling and simulation of the power system using the Electrical Transient Analyzer Program (ETAP) software. Technical system data, including transformer capacity, distribution network configuration, and load parameters, are modeled in the form of a Single Line Diagram (SLD) and analyzed using the Harmonic Load Flow module. The simulation results indicate that VSD operation produces dominant harmonics at the 5th and 7th orders, which significantly increase the THD levels within the system. The implementation of a passive single-tuned harmonic filter is shown to effectively reduce harmonic distortion, allowing the THD-I and THD-V values to approach or comply with the limits specified in the IEEE 519-2014 standard. Therefore, the application of appropriate harmonic mitigation methods can improve power quality, enhance energy efficiency, and increase the reliability of electrical power systems in distribution networks.